Strategi Komunikasi Pemasaran pada Perusahaan Asuransi dalam Meningkatkan Jumlah Nasabah - Ridha Nuzulyani; Yusuf, Raidah Intizar; Sabaruddin (Jurnal Publisitas, 2023)
This research aims to describe the marketing communication strategies implemented by PT. Asuransi Tugu Pratama Indonesia Tbk Cabang Makassar to enhance its customer base. In the context of marketing communication theory introduced by experts such as Philip Kotler and Kevin Lane Keller, the company adopts direct marketing by building strong relationships, aligning with the concept of customer relationship. Word-of-mouth marketing is emphasized to expand customer reach, following the principles outlined by Kotler and Keller. The maintenance of a positive corporate image and brand enhancement through public relations and sponsorship activities is also a focus, in line with the brand management concept described by Kotler and Keller. The use of online platforms and social media, such as Facebook and Instagram, reflects the company's adaptation to the development of digital marketing. Several supporting factors in this strategy include diverse products, strategic locations, attractive promotions, and technology, while the company also faces challenges such as the lack of awareness and trust in insurance within the community.